2013
DOI: 10.1039/c2an36264c
|View full text |Cite
|
Sign up to set email alerts
|

A bio-inspired sensor based on surfactant film and Pd nanoparticles

Abstract: A bio-inspired complex, [(bpbpmp)Fe(III)(m-OAc)(2)Cu(II)](ClO(4)), was combined with a zwitterionic surfactant (ImS3-14) stabilizing pre-formed palladium nanoparticles and coated on a glassy carbon electrode (GCE). This bio-inspired surfactant film was capable of catalyzing redox reactions of dihydroxybenzenes, thus allowing the simultaneous electrochemical quantification of CC and HQ in cigarette residue samples by square-wave voltammetry (SWV). The best experimental conditions were obtained using phosphate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…The long chain of aliphatic hydrocarbons present in the structure of this molecule interacts preferentially with the glassy carbon surface through van der Waals interactions, which facilitates the adsorption of the 10PyI molecule onto this surface. This behavior can be compared to films of surfactants (in reverse micelles systems) on carbon electrodes 15, 55, 56.…”
Section: Resultsmentioning
confidence: 99%
“…The long chain of aliphatic hydrocarbons present in the structure of this molecule interacts preferentially with the glassy carbon surface through van der Waals interactions, which facilitates the adsorption of the 10PyI molecule onto this surface. This behavior can be compared to films of surfactants (in reverse micelles systems) on carbon electrodes 15, 55, 56.…”
Section: Resultsmentioning
confidence: 99%
“…Palladium and gold nanoparticles prepared by RMs method and stabilized by using the same surfactant were used in development of electrochemical sensors for hydroquinone and catechol determination [166,167]. Zapp et al have reported the modification of a glassy carbon electrode with a bio-complex based on palladium nanoparticles stabilized with zwitterionic surfactant for simultaneous electrochemical determination of catechol and hydroquinone in cigarrete residue samples [166].…”
Section: Nanomaterials Synthesis Using Rms For Development Of Nanosenmentioning
confidence: 99%
“…Neste contexto, nos últimos anos tem-se observado o desenvolvimento de eletrodos bioinspirados, 33 monocamadas autorganizadas, 34 microfluídica, 35 e point-of-care test (POCT). 36 O emprego de nanopartículas magnéticas para pré-concentrar o analito de amostras complexas e o emprego da eletroanalítica em papel são alguns exemplos.…”
Section: Eletroanalíticaunclassified